Further evidence for sustained systemic inflammation in xenograft recipients (SIXR). (21st August 2015) - Iwase, Hayato; Ekser, Burcin; Zhou, Huidong; Liu, Hong; Satyananda, Vikas; Humar, Rishab; Humar, Pooja; Hara, Hidetaka; Long, Cassandra; Bhama, Jay K.; Bajona, Pietro; Wang, Yi; et al.
Abstract Introduction In pig‐to‐baboon heart/artery patch transplantation models, adequate costimulation blockade prevents a T‐cell response. After heart transplantation, coagulation dysfunction (thrombocytopenia, reduced fibrinogen, increased D‐dimer) and inflammation (increased C‐reactive protein [CRP]) develop. We evaluated whether coagulation dysfunction and/or inflammation can be detected following pig artery patch transplantation. Methods Baboons received heart (n = 8) or artery patch (n = 16) transplants from genetically engineered pigs and a costimulation blockade‐based regimen. Heart grafts functioned for 15–130 days. Artery recipients were euthanized after 28–84 days. Platelet counts, fibrinogen, D‐dimer, and CRP were measured. Results Thrombocytopenia and reduced fibrinogen developed only in recipients of hearts not expressing a coagulation‐regulatory protein (n = 4), but not in other heart or patch recipients. However, in heart recipients (n = 8), there were sustained increases in D‐dimer (<0.5 to 1.9 ug/ml [P < 0.01]) and CRP (0.26–2.2 mg/dl [P < 0.01]). In recipients of artery patches, there were also sustained increases in D‐dimer (<0.5 to 1.4 ug/ml [P < 0.01]) and CRP (0.26 to 1.5 mg/dl [P < 0.001]). An IL‐6R antagonist suppressed the increase in CRP, but not D‐dimer. Conclusion The pig artery patch model has proved valuable for determining immunosuppressive regimens that prevent sensitization to pig antigens. This model also provides information on the sustained systemic inflammation in xenograft recipients (SIXR). An IL‐6R antagonist may help suppress this response.